Assessment method of bench joints made of wood-based composites. (May 2015) - Smardzewski, Jerzy; İmirzi, Hasan Özgür and Lange, Julia and Podskarbi, Marcin
Abstract: So far, no coherent and comprehensive method has been elaborated allowing investigation of skeleton furniture made of wood and wood-based materials whose components are joined by means of screws. A world furniture manufacturer whose product development headquarters are situated in Poland has become interested in the quality assessment of such furniture joints. Therefore, the objective of this research project was: elaboration of an assessment method of screw joints which connect the seat panel with the horizontal rails of the bench; determination of stiffness and strength of these joints and assessment of the impact of the kind of the applied screw connectors on bench stiffness and strength. The performed experiments revealed that the strength of screw joints depended on the total area of pressure and shear. These, in turn, depended on the screw thread diameter, number of coils as well as coil inclination angle. The elaborated method allows: an objective evaluation of the construction quality and selection of the most advantageous connection for the furniture designed in future.